Diverse fluvial aggradation and incision response to interglacial—Glacial transitions in the headwaters of the Yangtze River, SE Tibetan Plateau - Yu, Yang; Wang, Xianyan; Yang, Xun; Yi, Shuangwen; Lu, Huayu (Geomorphology (Amsterdam, Netherlands), 2024)
As a key geomorphic archive, staircase sequences of terraces and sediments record the history of fluvial aggradation and incision, which are related to tectonic activities, climatic fluctuations, and varying base levels. While numerous studies have investigated their influence on the formation of fluvial terraces, the manner in which rivers adapt to diverse climatic transitions (specifically, the shifts from warm to cold and from cold to warm) remains a subject of ongoing debate, particularly when considered within varying tectonic and climatic contexts. Here, we address this issue by reconstructing terrace distributions and identifying sedimentary features with OSL dating in the headwaters of the Yangtze River in the southeastern Tibetan Plateau. We discovered two distinct sets of thick valley-filling sequences at different elevations indicating two phases of aggradation during the penultimate and last glacial periods, when the Yangtze River was in a transport-limited condition. During the warmer interglacial and deglacial periods, increased monsoon precipitation led to higher discharge, causing the river to incise into these valley fills. In addition, superimposed tectonic activities produced diverse river response to the climatic transition from interglacial to glacial between the upstream shallow valley and the downstream deeply incised gorge. In the upper valley, stable tectonic conditions resulted in minimal incision, with younger deposits overlying older ones. Conversely, in the downstream gorge, with more intense tectonic activities, sediments only partially covered the riverbed. These sediments acted as abrasion tools, facilitating rapid incision during the warm-to-cold transition, thereby creating two separated valley fills. This finding enhances our understanding of how tectonic forces influence river responses to interglacial—glacial cycles.